Kajian efektivitas kapasitas kerja pada kegiatan pemeliharaan common area di Kawasan Pariwisata The Nusa Dua, Bali - Makhmud, Desy Fatmala; Radnawati, Daisy; Syahadat, Ray March (Jurnal Arsitektur Lansekap, 2020)
Study on the Effectiveness of Work Capacity in Common Area Maintenance Activities in The Nusa Dua Tourism Area, Bali. Maintenance of Green Open Space (RTH) in an area is very important to do. In the current development of tourism, the existence of a good green space will not only improve the quality of the surrounding environment, but also can increase the sale value of an area if managed effectively and efficiently. The Nusa Dua tourism area managed by PT ITDC is an international tourist destination that has natural resources and good landscape management. RTH (Common Area) maintenance work is the main focus for The Nusa Dua Field Maintenance Unit (UPL). To determine the appropriateness of the standards for The Nusa Dua landscape maintenance work, a study will be conducted on the Effectiveness of Work Capacity of each type of maintenance work in the Common Area (CA) block. The study is limited to the Common Area 1-6 block, Nusa Dharma Island and Peninsula Island. The maintenance work that will be discussed is daily routine work by CA block workers. The stages start from preparation, data collection, analysis, and synthesis. Data collection techniques were carried out by means of observation, interviews, and literature studies. Data were analyzed qualitatively and quantitatively. The results obtained indicate the number of workers is still not in accordance with the standards in CA maintenance activities.